ASSOCIATION OF THE LEPTIN RECEPTOR Q223R GENE POLYMORPHISM AND FASTING PLASMA GLUCOSE LEVELS IN NORTH BULGARIAN SUBJECTS - Tihomir Rashev; Vladislav Nankov; Desislava Marinova; Stefan Trifonov (Journal of IMAB)
Purpose: Obesity, diabetes, and insulin resistance are growing public health concerns, and their incidences are constantly increasing. Imbalances in whole body glucose and insulin homeostasis are also closely linked to the trend of increased obesity. A number of single nucleotide polymorphisms (SNPs) of the coding region of the leptin receptor (LEPR) gene have been described and associated with obesity measures in different ethnic groups. In Q223R polymorphism, there is a non-conservative A to G substitution at codon 223, resulting in the replacement of glutamine with arginine amino acid. This changes the binding affinity of LEPR and impairs leptin signaling. The aim of the present study was to investigate the association between the Q223R SNP and obesity related anthropometric and biochemical parameters in the North Bulgarian population. Material/Methods. The study included 156 subjects. Body weight, body mass index and blood pressure were measured, and levels of fasting plasma glucose (FPG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL) and low-density lipoprotein cholesterol (LDL) were determined. Genotyping was performed by polymerase chain reaction-restriction fragment length polymorphism. Results. The results showed a significant association between the GG genotype of the LEPR Q223R polymorphism and elevated FPG levels. However, no association was found between LEPR genotypes and obesity status, HDL, LDL, or TC levels in North Bulgarian participants. Conclusions. The homozygous GG genotype of the LEPR Q223R polymorphism is associated with higher fasting plasma glucose levels and may be a predisposing factor for type 2 diabetes mellitus.